DAMAGE OF THE SPITTLEBUG Deois flavopicta (STAL) (HEMIPTERA:CERCOPIDAE) TO MAIZE IN INTERCROPPING SYSTEM WITH BRACHIARIA GRASS - CRUZ, IVAN; SILVA, IVANA FERNANDES DA; PAULA, CRISTIANE SOUZA; FIGUEIREDO, MARIA DE LOURDES CORRÊA; GONTIJO NETO, MIGUEL MARQUES; SILVA, RAFAEL BRAGA DA (International Journal of Maize & Sorghum, 2010)
One of the possibilities of recovering degraded areas intended for cattle raising is the maize-Brachiaria spp integration. In this system, it recovers soil fertility through the correct use of lime and adequate fertilizer replacement. The plantation of the two agricultural explorations is made simultaneously. However, the presence of some insect-pest common to both crops can reduce the efficiency of the integrated process. One of these insects is the spittlebug, Deois flavopicta, a sucking insect causing damage to the pastures both, through nymph and adult feeding. In maize only the adult causes damage, attacking the plant soon after its emergence. The experiment was done with the maize in the V2 phase, confining for a period of eight days a density of two adult spittlebugs/maize plant, kept alone or in association with Brachiaria species, being two susceptible (Brachiaria decumbens cv. Basilisk and B. ruziziensis cv. ruziziensis), and one resistant (B. brizantha cv. Marandu). In general the maize in monoculture was significantly damaged by the pest, reducing its development and showing more than 70% of yellowish leaves. The presence of Brachiaria grasses intercropped to maize plants reduced the spittlebug damage to these plants. In the presence of susceptible cultivar, such as B. decumbens, the damage to maize plant was lower than when together with the resistant cultivar B. brizantha.